2002
DOI: 10.1046/j.1365-2559.2002.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour `budding' as an index to estimate the potential of aggressiveness in rectal cancer

Abstract: Because of its value as a prognostic indicator and its reproducibility, tumour 'budding' would be a good index to estimate the aggressiveness of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
663
9
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 571 publications
(733 citation statements)
references
References 12 publications
31
663
9
18
Order By: Relevance
“…The presence of infiltrating growth pattern appears to be similar to the phenomenon known as dedifferentiation, where there is a dissociation of tumour cells at the invasive front allowing these cells to migrate away from the main tumour, which may represent a morphological assessment of 'tumour aggressiveness' 22 . This feature has also recently been described as 'tumour budding' where there is a transition from glandular structures to single cells or clusters of up to four cells the invasive margin of colorectal tumours 23 . A high-grade local immune response may represent effective host cellular immune responses preventing the invasive margin from developing an infiltrating or budding appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of infiltrating growth pattern appears to be similar to the phenomenon known as dedifferentiation, where there is a dissociation of tumour cells at the invasive front allowing these cells to migrate away from the main tumour, which may represent a morphological assessment of 'tumour aggressiveness' 22 . This feature has also recently been described as 'tumour budding' where there is a transition from glandular structures to single cells or clusters of up to four cells the invasive margin of colorectal tumours 23 . A high-grade local immune response may represent effective host cellular immune responses preventing the invasive margin from developing an infiltrating or budding appearance.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] On multivariate analysis, budding has consistently emerged as an independent adverse prognostic factor, associated with local tumor recurrence and distant metastases, and significantly worse overall and disease-free survival. 12,15,16,21,27,28,31,32,[34][35][36]38,40,41 The adverse prognostic impact of high-grade tumor budding is seen in both early and advanced colorectal carcinoma, and there are several scenarios in which this feature might influence clinical decision making, particularly in early colorectal carcinoma.…”
Section: Clinical Significance Of Tumor Buddingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor budding is another histopathological parameter, that has been recognized as an adverse prognostic factor in several human cancers like colorectal, oesophageal, laryngeal cancers and more recently tongue cancers [9][10][11][12][13][14]. It is defined as presence of isolated single cells or small cell clusters scattered in the stroma ahead of the ITF and is characteristic of aggressive cancer.…”
Section: Introductionmentioning
confidence: 99%